Whole exome sequencing reveals a missense mutation in the ADA gene causing severe combined immune deficiency in a Pakistani family ADA gene mutation causing SCID - Zara Khalid Khan; Sadaf Jafar; Sheeba Shabbir; Muhammad Zeeshan Anwar; Rabea Nasir; Attea Zaman; Momin Iqbal; Syed Irfan Raza (Journal of University Medical & Dental College, 2023)
BACKGROUND & OBJECTIVE: Human adenosine deaminase deficiency, OMIM 102700 (ADA deficiency) is a genetic disorder which causes severe combined immunodeficiency (SCID). The enzyme adenosine deaminase is a housekeeping in nature and is involved in purine catabolism by catalyzing irreversible deamination of adenosine and deoxyadenosine. The SCID patients’ immune system is unable to fight off most of the bacterial and fungal infections due to profound lymphopenia (T-B-NK+). About 20% of the SCID patients are genetically homozygous for defective ADA gene. In our study we aimed to find out genetic variant in ADA gene in a family carrying severe combined immune deficiency. Objective in the current study is to unravel and characterize the molecular cause of the patient suffering from by birth SCID.METHODOLOGY: In the present study we enrolled a 6-month-old female SCID patient belonging to highly consanguineous Pakistani family. Patient clinical features included repeated chest infection with failure to thrive, fever and chronic diarrhea. Whole blood samples from patient, parents and healthy siblings were acquired in EDTA tubes. DNA was extracted from all the blood samples.RESULTS: Flowcytometry revealed lymphopenia (T-B-NK+) type of SCID. Whole Exome Sequencing (WES) identified a one nucleotide change (c.716G>A) in ADA gene exon 8. The segregation of the identified variant in the family was confirmed through Sanger Sequencing.CONCLUSION: In this study, we presented detailed clinical and genetic description of patient suffering from severe combined immune deficiency. The immunological and genetic findings presented in this study will facilitate early diagnosis of the disease. Segregation of the identified variant in the family members will also aid in genetic counseling the family.